Clinical features, biochemistry, and HLA‐DRB1 status in youth‐onset type 1 diabetes in Sudan. Issue 5 (20th April 2021) - Ibrahim, Tomader Ali Mohammed; Govender, Denira; Abdullah, Mohamed Ahmed; Noble, Janelle Annette; Hussien, Mohammed Osman; Lane, Julie Ann; Mack, Steven John; Martin, Gregory George Noble; Atkinson, Mark Alvin; Wasserfall, Clive Henry; Ogle, Graham David
Abstract: Objective: To further understand clinical and biochemical features, and HLA‐DRB1 genotypes, in new cases of diabetes in Sudanese children and adolescents. Research Design and Methods: Demographic characteristics, clinical information, and biochemical parameters (blood glucose, HbA1c, C‐peptide, autoantibodies against glutamic acid decarboxylase 65 [GADA] and insulinoma‐associated protein‐2 [IA‐2A], and HLA‐DRB1 ) were assessed in 99 individuals <18 years, recently (<18 months) clinically diagnosed with T1D. HLA‐DRB1 genotypes for 56 of these Arab individuals with T1D were compared to a mixed control group of 198 healthy Arab (75%) and African (25%) individuals without T1D. Results: Mean ± SD age at diagnosis was 10.1 ± 4.3 years (range 0.7–17.6 years) with mode at 9–12 years. A female preponderance was observed. Fifty‐two individuals (55.3%) presented in diabetic ketoacidosis (DKA). Mean ± SD serum fasting C‐peptide values were 0.22 ± 0.25 nmol/L (0.66±0.74 ng/ml). 31.3% were autoantibody negative, 53.4% were GADA positive, 27.2% were IA‐2A positive, with 12.1% positive for both autoantibodies. Association analysis compared to 198 controls of similar ethnic origin revealed strong locus association with HLA‐DRB1 (p < 2.4 × 10 –14 ). Five HLA‐DRB1 alleles exhibited significant T1D association: three alleles ( DRB1*03:01, DRB1*04:02, and DRB1*04:05 ) were positively associated, while three ( DRB1*10:01, DRB1*15:02, and DRB1*15:03 ) were protective. DRB1*03:01 had the strongest association (odds ratio = 5.04, p = 1.7 × 10 –10 ). Conclusions: Young Sudanese individuals with T1D generally have similar characteristics to reported European‐origin T1D populations. However, they have higher rates of DKA and slightly lower autoantibody rates than reported European‐origin populations, and a particularly strong association with HLA‐DRB1*03:01 .